A focus group study exploring student nurse's experiences of an educational intervention focused on working with people with a diagnosis of personality disorder. Issue 7 (16th July 2018) - Stacey, Gemma; Baldwin, Vicky; Thompson, Benjamin J.; Aubeeluck, Aimee
Accessible summary: What is known on the subject?: Research has consistently shown that poor attitudes exist in mental health care towards people with a diagnosis of personality disorder and that nurses can find working with this group of patients professionally and personally challenging. Power imbalances of practitioner over students exist on training placements. This can result in students being exposed to negative attitudes towards service users with a diagnosis of personality disorder and not feeling able to challenge these attitudes. The Knowledge and Understanding Framework (KUF) is a specialist programme of personality disorder training that has demonstrated effectiveness with qualified mental health professionals. What does this paper add to existing knowledge?: Although the subject of personality disorder is considered within preregistration education, an opportunity for a more robust approach to supporting student's nurses with this complex subject area is required (Ross & Goldner 2018). Attempts to integrate and evaluate specific educational interventions of this nature into preregistration nurse education have not been explored elsewhere. This study utilized focus groups to examine the experience of the KUF training and the perceived impact on attitudes and approaches to personality disorder of a group of nursing students who had completed the KUF programme. The students exhibited positive attitudes towards people with a diagnosis of personality disorder and confidence to influence negative attitudes in practice. The KUF shifted the students' focus from identifying patient behaviours as problematic towards an understanding of these difficulties arising from their own emotional responses. This was a small study so the results should be treated with caution. There was no follow‐up once the students had qualified, so it is not clear whether such effects would endure long term. What are the implications for practice?: Training students using the KUF may foster positive attitudes to people with a diagnosis of personality disorder and provide them with the skills to positively influence other colleagues practice. Abstract: Introduction: Negative attitudes exist in practice towards those with a diagnosis of personality disorder. Preregistration training offers the opportunity to address this by developing understanding of the diagnosis, confidence in working with people with the diagnosis and empowering new nurses to challenge prevailing attitudes. Attempts to integrate and evaluate specific educational interventions of this nature into preregistration nurse education have not been explored elsewhere. Aim: To explore preregistration, nurses' experience of a programme of training focused on personality disorder and their perception of its influence on attitudes, understanding of clients and their experience of practice. Method: A qualitative study using thematic analysis of two focus groups of preregistration mental health nursing students. Results: Evidence of positive attitudes and confidence to supportively challenge negative attitudes in practice were found. Students showed a shift away from a focus on changing the perceived "difficult" behaviour of a client towards an understanding of their own emotional responses to the behaviours. Discussion: The Knowledge and Understanding Framework training shows potential for students to change attitudes and develop progressive practice working with people with personality disorder. Implications for practice: The integration of the Knowledge and Understanding Framework should be considered as part of preregistration training. Further research into the sustained influence of the training post registration is required.